The Impact of Strategic Agility on MSMEs Innovation Driven by Digital Entrepreneurial Leadership - Jufri Ali; Hadiwibowo Imam (E3S Web of Conferences)
The research explores the impact of strategic agility on the innovation of micro, small, and medium enterprises (MSMEs), mediated by digital entrepreneurial leadership. In the rapidly evolving era of digitalization, MSMEs face the challenge of remaining adaptive to market and technological changes. Strategic agility is the organization's ability to respond to environmental changes quickly and effectively, a key factor in supporting sustainable innovation. Digital entrepreneurial leadership plays an important role in driving the utilization of digital technology and creating new opportunities through innovation. This study employs a quantitative approach, collecting data from Batik MSMEs in West Java, such as Cirebon (Batik Megamendung), Garut (Batik Garutan), Tasikmalaya (Batik Tasik), Batik Bogor, Indramayu (Batik Dermayon), Batik Sumedang, and Batik Bandung. SmartPLS processes the data using statistical analysis methods to analyze the relationship between strategic agility, digital leadership, and innovation. The research results demonstrate a significant positive impact of strategic agility on MSMEs innovation, which digital entrepreneurial leadership reinforces. This article provides theoretical and practical contributions to understanding the importance of combining strategy and technology-based leadership in developing the competitiveness of MSMEs in the digital era.